Utilization of the response surface methodology to model changes in the productivity of Cynodon nlemfuensis Vanderyst - Fernandez-Dominguez, Liansy; del Pozo-Rodriguez, Pedro Pablo; Fernandez-Chuairey, Lucia; Herrera-Garcia, Rafael Segundo (Pastos y forrajes, 2020)
Objective: To use the response surface methodology to model the productivity changes of Cynodon nlemfuensis Vanderyst, subject to different fertilization doses and regrowth ages, under cutting conditions, in both seasons of the year. Materials and Methods: The data were taken from experiments conducted at the Institute of Animal Science in a split-plot design. The main plot was the nitrogen application dose (0,200 and 400 kg N/ha/year). Meanwhile, in the subplots, the 12 regrowth ages (from 1 to 12 weeks) were placed. The total dry matter yield, leaf dry matter yield and stem dry matter yield, were analyzed as response variables. The data were adjusted to multiple regression and response surface models for each variable. They were statistically processed through the packages STATGRAPHICS[R] Centurion XVI and GeoGebra. Results: The variables total dry mater yield, leaf dry matter yield and stem dry matter yield, for the dry and rainy seasons, normally decreased for the magnitude of the standardized biases and kurtosis. The second-order model was of good fit, with determination coefficient ([R.sup.2]) higher than 94 % for all the variables, whose expressions allowed to analyze integrally the management factors in the productive performance of pasture, which facilitates decisionmaking for its management. Conclusions: It was proven that the procedures associated to the response surface methodology constitute an efficient tool for pasture growth analysis. Keywords: Cynodon nlemfuensis, experimentation, mathematical models, productivity